Avascular Necrosis of the Femoral Head: A Case Report with Emphasis on Imaging Findings - Ansari, S; Dhungel, K; Ahmad, K; Gupta, MK; Amanullah, MF; Rauniyar, RK (Nepalese Journal of Radiology, 2013)
Avascular necrosis (AVN) of the femoral head is a disease caused by reduced blood supply to the subchondral bone leading to destruction of the hip joint. Most common sites are femoral and humeral head. Initially, patients are asymptomatic, but, in time, AVN leads to joint destruction, requiring surgical treatment and, in later stages, total hip replacement. Magnetic resonance imaging (MRI) has been proved to be a highly accurate method both for early diagnosis and for staging of the disease. We present a case of avascular necrosis of right femoral head in 28 year old male following trauma to hip. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 92-95 DOI: http://dx.doi.org/10.3126/njr.v2i2.7694